2006
DOI: 10.1111/j.1460-9568.2006.05059.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor (BDNF) is required for the enhancement of hippocampal neurogenesis following environmental enrichment

Abstract: Neurogenesis continues to occur in the adult mammalian hippocampus and is regulated by both genetic and environmental factors. It is known that exposure to an enriched environment enhances the number of newly generated neurons in the dentate gyrus. However, the mechanisms by which enriched housing produces these effects are poorly understood. To test a role for neurotrophins, we used heterozygous knockout mice for brain-derived neurotrophic factor (BDNF+/-) and mice lacking neurotrophin-4 (NT-4-/-) together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
357
1
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(387 citation statements)
references
References 44 publications
15
357
1
14
Order By: Relevance
“…EE promotes various plasticity mechanisms in the hippocampus, including bdnf gene upregulation, enhanced dendritic branching, and the stimulation of adult neurogenesis [234][235][236][237], reminiscent of our observations that CSP-TTK21 activates CBP/p300 activity. Furthermore, CBP-deficient mice present no response to the beneficial effect of EE on the induction and enhancement of spatial navigation capabilities during neurogenesis, highlighting the contribution of CBP to EE effects [233].…”
Section: Discussionsupporting
confidence: 71%
“…EE promotes various plasticity mechanisms in the hippocampus, including bdnf gene upregulation, enhanced dendritic branching, and the stimulation of adult neurogenesis [234][235][236][237], reminiscent of our observations that CSP-TTK21 activates CBP/p300 activity. Furthermore, CBP-deficient mice present no response to the beneficial effect of EE on the induction and enhancement of spatial navigation capabilities during neurogenesis, highlighting the contribution of CBP to EE effects [233].…”
Section: Discussionsupporting
confidence: 71%
“…This antidepressantinduced survival is lost in mice with impaired BDNF signaling (Sairanen et al, 2005). An additional study found evidence for the dependence of BDNF on the enhancement of hippocampal neurogenesis that is observed following environmental enrichment (Rossi et al, 2006).…”
Section: Bdnfmentioning
confidence: 94%
“…Exposure of mice to an enriched environment or a running wheel increases both the spatial memory ability in the water maze and the number of adult-born neurons in DG (Kempermann et al 1997(Kempermann et al , 1998aNilsson et al 1999;van Praag et al 1999a,b;Brown et al 2003;Koo et al 2003;Rossi et al 2006;Tashiro et al 2007). In addition, both neurogenesis and spatial memory performances are improved in senescent or middle-aged mice raised in an enriched environment (Kempermann et al 1998b.…”
Section: Correlationsmentioning
confidence: 99%